2015
DOI: 10.1136/openhrt-2014-000088
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a PCI Bleeding Risk Score in patient subsets stratified for body mass index

Abstract: ObjectiveAn accurate tool with good discriminative for bleeding would be useful to clinicians for improved management of all their patients. Bleeding risk models have been published but not externally validated in independent clinical data set. We chose the National Cardiovascular Data Registry (NCDR) percutaneous coronary intervention (PCI) score to validate within a large, multisite community data set. The aim of the study was validation of this Bleeding Risk Score (BRS) tool among a subgroup of patients bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Current rates of major bleeding are below 2% on average and other studies have suggested equivalent bleeding rates between access site when bivalirudin is used. 2 17 18 This finding is confirmed in this large multisite clinical registry. Among 58 862 PCI procedures of all comers across 137 hospitals, our analysis demonstrated no difference in major bleeding rates for patients receiving bivalirudin ( figure 2 ).…”
Section: Discussionsupporting
confidence: 79%
“…Current rates of major bleeding are below 2% on average and other studies have suggested equivalent bleeding rates between access site when bivalirudin is used. 2 17 18 This finding is confirmed in this large multisite clinical registry. Among 58 862 PCI procedures of all comers across 137 hospitals, our analysis demonstrated no difference in major bleeding rates for patients receiving bivalirudin ( figure 2 ).…”
Section: Discussionsupporting
confidence: 79%
“…The use of a bare steel needle, which aids in reducing the puncture angle to increase the contact area between the needle and blood vessel, may be beneficial for improving the success rate. Moreover, studies [ 26 , 27 ] have shown that low BMI is strongly correlated with adverse cardiovascular events and that low BMI increases the risk of bleeding after coronary stenting. However, there are few studies on the safety and efficacy of coronary intervention via dTRA (compared with cTRA) in patients with low BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Though these procedures are lifesaving, if done in patients who suffer from chest pain due to noncoronary artery disease related lesions, they may prove unnecessary adding to expenses, waste of resources, and lead to life threatening complications as well as. [1][2][3][4] The ST segment is the flat, iso-electric section of the ECG which represents the interval between ventricular depolarization and repolarization. 5 Injury currents flowing from the depolarized ischemic regions to normal regions result in the appearance of ST segment elevation where the ischemic region is transmural.…”
Section: Introductionmentioning
confidence: 99%